2015
DOI: 10.1371/journal.pone.0129134
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of FMDv Releases from the National Bio and Agro Defense Facility

Abstract: This study evaluates the economic consequences of hypothetical foot-and-mouth disease releases from the future National Bio and Agro Defense Facility in Manhattan, Kansas. Using an economic framework that estimates the impacts to agricultural firms and consumers, quantifies costs to non-agricultural activities in the epidemiologically impacted region, and assesses costs of response to the government, we find the distribution of economic impacts to be very significant. Furthermore, agricultural firms and consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Depending on the characteristics of the diseases (infectiousness, morbidity, lethality) and their consequences (individual, local, global level), the losses associated vary massively. As an example of highly and fast contagious disease, Pendell et al (2015) assessed the costs of a hypothetic outbreak of Foot and Mouth Disease in the United States, ranging from $16 to $140 billion. On the other hand, the costs of clinical mastitis generally affect only the afflicted herd, representing roughly a cost of $224 to $275 per case (Steeneveld et al, 2011).…”
Section: Factors Influencing Antimicrobial Use: the Crucial Issue Of mentioning
confidence: 99%
“…Depending on the characteristics of the diseases (infectiousness, morbidity, lethality) and their consequences (individual, local, global level), the losses associated vary massively. As an example of highly and fast contagious disease, Pendell et al (2015) assessed the costs of a hypothetic outbreak of Foot and Mouth Disease in the United States, ranging from $16 to $140 billion. On the other hand, the costs of clinical mastitis generally affect only the afflicted herd, representing roughly a cost of $224 to $275 per case (Steeneveld et al, 2011).…”
Section: Factors Influencing Antimicrobial Use: the Crucial Issue Of mentioning
confidence: 99%
“…Livestock are essential for food security, livelihoods, cultural identity and social status of small-scale farmers in Africa 5,6 , but endemic FMD circulation stifles economic growth and productivity, affecting food and economic security of the poorest families 5,7 . Economic losses from FMD include direct production losses alone of US$2.3 billion per year 8 , over 0.1% of sub-Saharan Africa's entire Gross Domestic Product 9 (where the disease is predominantly found), and indirect losses through restrictions on Africa's economic growth by impeding domestic and international trade 10 (where indirect losses to an economy from FMD can starkly overshadow production losses). Although these impacts have been described at an aggregate level, control policies targeting those most affected require an understanding of household-level impacts, incentives, and heterogeneities across production systems and regions.…”
Section: Introductionmentioning
confidence: 99%
“…devastating consequences to the country's economy. Several studies have modeled the 13 hypothetic FMD outbreak in the U.S. to estimate the potential economic loss. Pendell 14 et al estimated the financial loss of an outbreak constrained to Kansas would vary from 15 $43 to $706 million determined by the livestock species initially infected [11].…”
mentioning
confidence: 99%
“…Schroeder 16 et al reported a loss of as many as 7,000-8,000 livestock herds and 16-18 million 17 animals for a regional, central U.S. outbreak [12]. Pendell et al estimated a loss of 18 around $16-140 billion for an outbreak in the Midwestern U.S. originating from the 19 proposed National Bio and Agri-Defense Facility in Kansas [13]. 20 Liu et al [6] presented a spatially explicit agent-based simulator for synthesizing 21 beef cattle movements, and provided insight into the influence of network dynamics on 22 epidemic dynamics.…”
mentioning
confidence: 99%